Analysis on the Influence of Fire Overhangs on the Window to Exterior Wall Vertical Fire Plume Spreading under External Wind. (2016) - Wang, Tian-hao; Zhao, Hao; Zhou, Yang
Abstract: The blocked performance of the fire canopy to vertical fire plume spread was studied by 1/2 scale building external facade flame experiment and FDS numerical simulation, and the blocked performance of the fire canopy to vertical fire plume spread was studied under external wind by FDS. The results showed that when the extending length of the fire canopy reached 0.6 m, it could block the vertical spread of openings overflow fire plume effectively; when the wind speed reached 3 m/s, the height of windowsill walls reached 0.4 m, the fire canopy could still block vertical fire plume spread.